Livelihood vulnerability of pastoral households in the semiarid grasslands of northern China: Measurement and determinants. (July 2022) - Qin, Zhang; Haili, Xue; Xiao, Lan; Luwei, Dai; Bojie, Wang; Fengqi, Cui; Haiping, Tang
Highlights: Livelihood assets can serve as a focus point for addressing livelihood vulnerabilities. Ecological protection policies may increase the vulnerability of household livelihoods. A strong link between household life cycle and livelihood vulnerability. Abstract: Livelihood vulnerability assessment has become an important policy tool for identifying groups in need of immediate intervention. Based on survey data covering 427 households in the Hulunbuir Grasslands in northern China, an indicator-based livelihood vulnerability assessment system (LVAS) was established by combining the sustainable livelihood framework and the exposure–sensitivity–adaptation framework, which described the livelihood vulnerability of households across the household life cycle in terms of the dimensions of exposure, sensitivity, and adaptation. A multiple linear regression model was used to identify the key variables that determine livelihood vulnerability. The results show that the livelihoods of pastoral households in the Hulunbuir Grasslands are moderately vulnerable overall, with a high level of exposure, a medium level of sensitivity, and a low level of adaptive capacity. As the household life cycle progresses (from the starting period to the empty-nest period), the adaptive capacity of pastoral households gradually decreases, and their livelihood vulnerability increases. The variables that most exacerbate the vulnerability of pastoral households' livelihoods in this region are policy–ecological risks, climate–disaster risks and socioeconomic risks, and the main ways to reduce vulnerability are to improve these households' productive capital, diversify their sources of livelihood, and improve their access to information. The results of the study provide empirical support for similar settings in different regions worldwide that aim to achieve a "win–win" situation of ecological conservation and sustainable livelihood development.